Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Discovery Learning Pada Materi Bangun Datar Segiempat - Toga, Eriska Rambu Kareri; Yulius Keremata Lede; Making, Samuel Rex M; Lubur, Dorothea Novia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The low results of mathematics learning in school today include the use of LKPD which is not yet optimal. Apart from that, the LKPD used is not optimally based on discovery learning. One of the teaching materials that can overcome this problem is LKPD based on discovery learning. The aim of this research of this to produce of LKPD based on discovery learning models on flat rectangulars shapes. This type of research is research and development with the object of research being LKPD based on discovery learning. The data collection instrument in this research are expert validation sheets by expert validation to determine product validation and student response questionnaires to determine the practicality of LKPD based on discovery learning. The data analysis techniques used are qualitative analysis techniques and quantitative data analysis technique. Based on data analysis, two results of this research can be stated. First, LKPD based on discovery learning was declared valed and suitable for use in the mathematics learning process. This is shown by the average expert validity of 3.32. Second, the use of mathematics teaching materials in class VII A students learning at SMP Negeri 1 Kota Tambolaka is practical with an average practicality value of 3,58